TRANSFORMASI PENULISAN : Bahasa Malaysia SPM - Azizul Rahman Abdul Rahman, author; Mariam Mehad, author.; Mohd. Azam Ahmad,eauthor (Bandar Baru Bangi, Selangor : Penerbitan Pelangi Sdn. Bhd., 2016)
PSZJBL